Improvement of microclimatic working conditions for miners in deep mines (Rudarsko-geološko-naftni zbornik, 2024)
The purpose of the paper is to substantiate possible ways to improve microclimatic conditions at workplaces in deep coal mines by controlling air moisture content. To improve the microclimatic conditions at underground workplaces, the authors propose a unit for dehumidification of air in a blind mine working, which is designed to remove moisture contained in mine air in the form of steam. The results of the calculations showed that by air dehumidification in a blind working, which is supplied by a local ventilation unit at a temperature of 24°C, and then cooled below the dew point and supplied to the face at a temperature of 20°C, the microclimatic index Humidex decreases from a dangerous level of 37.66 to a comfortable level of 12.5. The proposed method of normalising the working conditions of miners in deep mines, with an integrated approach that includes temperature conditioning with simultaneous extraction of high-quality water, as well as facilitating the ventilation regime in mine workings, provides significant benefits in terms of industrial sanitation, technology, and economics.